Utilization Patterns of Perioperative Neuromuscular Blockade Reversal in the United States: A Retrospective Observational Study From the Multicenter Perioperative Outcomes Group. (November 2020) - Dubovoy, Timur Z.; Saager, Leif; Shah, Nirav J.; Colquhoun, Douglas A.; Mathis, Michael R.; Kapeles, Steven; Mentz, Graciela; Kheterpal, Sachin; Vaughn, Michelle T.
Abstract : BACKGROUND: Following the introduction of sugammadex to the US clinical practice, scarce data are available to understand its utilization patterns. This study aimed to characterize patient, procedure, and provider factors associated with sugammadex administration in US patients. METHODS: This retrospective observational study was conducted across 24 Multicenter Perioperative Outcomes Group institutions in the United States with sugammadex on formulary at the time of the study. All American Society of Anesthesiologists (ASA) physical status I–IV adults undergoing noncardiac surgery from 2014 to 2018 receiving neuromuscular blockade (NMB) were eligible. The study established 3 periods based on the date of first documented sugammadex use at each institution: the presugammadex period, 0- to 6-month transitional period, and 6+ months postsugammadex period. The primary outcome was reversal using sugammadex during the postsugammadex period—defined as 6 months after sugammadex was first utilized at each institution. A multivariable mixed-effects logistic regression model controlling for institution was developed to assess patient, procedure, and provider factors associated with sugammadex administration. RESULTS: A total of 934, 798 cases met inclusion criteria. Following the 6-month transitional period, sugammadex was used on average in 40.0% (95% confidence interval [CI], 39.8–40.2) of cases receiving NMB. Multivariable analysis demonstrated sugammadex use to be associated with train-of-four count of 0–1 (adjusted odds ratio = 4.06; 95% CI, 33.83–4.31) or 2 (2.45; 2.29–2.62) vs 3–4 twitches before reversal; the amount of NMB administered (3.01; 2.88–3.16) for the highest effective dose 95 quartile compared to the lowest quartile; advanced age (1.83; 1.71–1.95) compared to age <41; male sex (1.36; 1.32–1.39) compared to female sex; major thoracic surgery (1.26; 1.13–1.39); congestive heart failure (1.17, 1.07–1.28); and ASA III or IV (1.13; 1.10–1.16) versus ASA I or II. CONCLUSIONS: Our data demonstrate broad early clinical adoption of sugammadex following Food and Drug Administration approval. Sugammadex is used preferentially in cases with higher degrees of NMB before reversal and in patients with greater burden of comorbidities and known risk factors for residual blockade or pulmonary complications.